2011
DOI: 10.3349/ymj.2011.52.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Taiwanese Female Vegetarians Have Lower Lipoprotein-Associated Phospholipase A2 Compared with Omnivores

Abstract: PurposeMany studies supported that vegetarians have a lower risk of cardiac diseases and mortality, partly due to better blood pressure and serum cholesterol profiles. However, the inflammatory markers, especially lipoprotein-associated phospholipase A2 (Lp-PLA2), have not been well-studied. This study aimed to compare inflammatory markers and conventional risk factors between vegetarians and omnivores.Materials and MethodsOne hundred and seventy-three vegetarians and 190 omnivores were studied. Fasting blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Seven studies implemented a >2-year duration of vegetarianism (10)(11)(12)(13)29,32,33) . Eight studies reported lower concentrations of inflammatory marker(s) in vegetarians v. omnivores (9)(10)(11)(12)(13)28,29,31) , seven studies found no difference between groups (19,30,(32)(33)(34)(35)(36) , and three studies reported higher concentrations of inflammatory marker(s) in vegetarians v. omnivores (18,20,37) .…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies implemented a >2-year duration of vegetarianism (10)(11)(12)(13)29,32,33) . Eight studies reported lower concentrations of inflammatory marker(s) in vegetarians v. omnivores (9)(10)(11)(12)(13)28,29,31) , seven studies found no difference between groups (19,30,(32)(33)(34)(35)(36) , and three studies reported higher concentrations of inflammatory marker(s) in vegetarians v. omnivores (18,20,37) .…”
Section: Systematic Reviewmentioning
confidence: 99%
“…A meta-analysis was performed on seventeen studies including a total of 2398 subjects (9)(10)(11)(12)(13)(18)(19)(20)(28)(29)(30)(32)(33)(34)(35)(36)(37) ; the study by Paalani et al (31) was not included in the metaanalysis because data were reported as median and interquartile range. Pooled effect size showed that there was no difference in hs-CRP levels in vegetarians v. Fig.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…§ In 20 studies, diets were assessed by using questionnaires, typic ally food frequency questionnaires 17,29,32,34,35,38,40 or 24-hour diet recalls. { Interviews or self-report were used in 7 studies, 18,19,24,28,36,43,47 and weighing methods were used for 1 study 21 ; the means of dietary assessment were not reported in 4 studies. 23,26,30,46 Of the 32 observational studies, 12 conducted repeated measurements of BP.# The adjusted factors in each study are shown in the Supplement (eTable 2).…”
Section: Observational Studiesmentioning
confidence: 99%
“…Vegetarian diets have long been considered beneficial for health. Several investigators have shown that vegetarian diets have a positive impact in altering serum lipids, reducing blood pressure, improving glycemia control and insulin sensitivity, reducing weight, and lowering mortality [ 12 , 13 ]. However, other studies have found no beneficial effects and indicated that vegetarian diets were associated with the development of subclinical protein malnutrition and vitamin deficiency [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%